Glue ear, hearing loss and IQ: an association moderated by the child's home environment. - Amanda J Hall; Richard Maw; Elizabeth Midgley; Jean Golding; Colin Steer (PLoS ONE)
Background Glue ear or otitis media with effusion (OME) is common in children and may be associated with hearing loss (HL). For most children it has no long lasting effects on cognitive development but it is unclear whether there are subgroups at higher risk of sequelae. Objectives To examine the association between a score comprising the number of times a child had OME and HL (OME/HL score) in the first four/five years of life and IQ at age 4 and 8. To examine whether any association between OME/HL and IQ is moderated by socioeconomic, child or family factors. Methods Prospective, longitudinal cohort study: the Avon Longitudinal Study of Parents and Children (ALSPAC). 1155 children tested using tympanometry on up to nine occasions and hearing for speech (word recognition) on up to three occasions between age 8 months and 5 years. An OME/HL score was created and associations with IQ at ages 4 and 8 were examined. Potential moderators included a measure of the child's cognitive stimulation at home (HOME score). Results For the whole sample at age 4 the group with the highest 10% OME/HL scores had performance IQ 5 points lower [95% CI -9, -1] and verbal IQ 6 points lower [95% CI -10, -3] than the unaffected group. By age 8 the evidence for group differences was weak. There were significant interactions between OME/HL and the HOME score: those with high OME/HL scores and low 18 month HOME scores had lower IQ at age 4 and 8 than those with high OME/HL scores and high HOME scores. Adjusted mean differences ranged from 5 to 8 IQ points at age 4 and 8. Conclusions The cognitive development of children from homes with lower levels of cognitive stimulation is susceptible to the effects of glue ear and hearing loss.